Analysis of the Effect of Food Social Assistance and PIP on the Human Development Index in Indonesia - Triski Anawati; Retno Febriyastuti Widyawati (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the effect of government spending on realizing food social assistance and the Smart Indonesia Program (PIP) in Indonesia. This type of research is quantitative with the research locations of DKI Jakarta, DI Yogyakarta, Riau Islands, East Kalimantan, and Bali. This research uses secondary data from the Indonesian Central Bureau of Statistics and the Ministry of Education and Culture’s PIP. This study uses panel data regression analysis with the Panel Estimated Generalized Least Squares analysis method. The results of this study indicate that the social assistance distribution budget variable has a significant effect on the Human Development Index variable. In contrast, the Program Indonesia Pintar distribution budget variable does not affect the Human Development Index.